Why did they kill? : Cambodia in the shadow of genocide - Hinton, Alexander Laban (California series in public anthropology, 2005)
Of all the horrors human beings perpetrate, genocide stands near the top of the list. Its toll is staggering: well over 100 million dead worldwide. Why Did They Kill? is one of the first anthropological attempts to analyze the origins of genocide. In it, Alexander Hinton focuses on the devastation that took place in Cambodia from April 1975 to January 1979 under the Khmer Rouge in order to explore why mass murder happens and what motivates perpetrators to kill.